Towards hydrodynamic simulations of wet particle systems - Roy, Sudeshna; Luding, Stefan; Weinhart, Thomas (Procedia Engineering, 2015)
This paper presents the rheology of weakly wetted granular materials in the slow frictional regime, using Discrete Element Method (DEM) simulations. In a split-bottom ring shear cell geometry a slow, quasi-static deformation leads to wide shear bands away from the walls. Dry non-cohesive and cohesive materials are compared in order to understand the effect of liquid bridge capillary forces on the macroscopic flow properties. Different liquid contents lead to different flow curves when measuring the shear stress-strain relations, helping to understand the effect of wetness on the flow of granular materials.
Created from Fastlane, Scopus look-up
Keywords: DEM; Liquid bridge; Shear band; Slow flow rheology